Dentin erosive wear is reduced by fluoride varnishes containing nanosized sodium trimetaphosphate in vitro - Isabela Ferreira da SILVA; Letícia Cabrera CAPALBO; Renan DAL-FABBRO; Mayra Frasson PAIVA; Thayse Yumi HOSIDA; Liliana Carolina BÁEZ-QUINTERO; Caio SAMPAIO; Douglas Roberto MONTEIRO; Alberto Carlos Botazzo DELBEM; Juliano Pelim PESSAN (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study evaluated the effect of fluoride varnishes containing micrometric or nanosized sodium trimetaphosphate (TMP) on dentin erosive wear in vitro. Bovine root dentin blocks were selected by surface hardness and randomly divided into five experimental groups/varnishes (n = 20/group): placebo, 5% sodium fluoride (NaF); 5% NaF+5% micrometric TMP; 5% NaF+2.5% nanosized TMP; and 5% NaF+5% nanosized TMP. Half of the surface of all blocks received a single application of the assigned varnish, with subsequent immersion in artificial saliva for 6 h. Varnishes were then removed and the blocks were immersed in citric acid (90 s, 4×/day, 5 days). After each erosive cycle, ten blocks of each group were immersed in a placebo dentifrice for 15 s (ERO), while the other ten blocks were subjected to abrasion by brushing (ERO+ABR). Dentin erosive wear was assessed by profilometry. Data were submitted to 2-way ANOVA and to the Holm-Sidak test (p<0.05). Dentin erosive wear was significantly higher for ERO+ABR than for ERO for all varnishes. TMP-containing varnishes promoted superior effects against dentin erosive wear compared with 5% NaF alone; and 5% nanosized TMP led to the lowest wear among all varnishes. In conclusion, the addition of TMP to conventional fluoride varnish (i.e., varnish containing only NaF) enhanced its protective effects against bovine root dentin erosion and erosion+abrasion. Additionally, the use of 5% nanosized TMP led to superior effects in comparison to 5% micrometric TMP, both for erosion and erosion+abrasion in vitro.